Semantics and application of speaking verbs - Syzdykova, Г.О. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Verbs are part of speech rich in semantic groups. The specificity of the semantic groups of verbs is determined by their function and use. The most common of these are verbs of speech. Speech verbs are associated with the act of speaking. Speech is a human process, a phenomenon that occurs through human interaction. The nature of the implementation of human speech, the process of transition, all aspects of general speech activity are determined by speech verbs. The nature, mode of transmission, form of speech, presentation of information - all this depends on the linguistic nature of speech verbs. The article discusses the meaning and application of the verbs "to speak", "say", "bring" in the Kazakh language. Their use in the process of speech, the features of use are determined by linguistic data.